THE EFFECT OF AUDIT TENURE, COMPANY SIZE, PUBLIC ACCOUNTING FIRM SIZE, AND INDEPENDENT COMMISSIONERS ON AUDIT DELAY IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2022–2024 PERIOD - Jenny Zain; Vanesa Tandri; Evani Artha; Hanicka Theneles; Enda Noviyanti Simorangkir; Oky Syahputra (RADJA PUBLIKA, 2026)
This study aims to examine the factors that may influence audit delay in banking companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024, and to draw conclusions based on the findings. The independent variables used in this study include audit tenure, company size, public accounting firm size, and independent commissioners, with audit delay as the dependent variable. This research employs a quantitative approach with a sample of 40 companies. The data analysis method uses multiple linear regression. A purposive sampling strategy was applied as the sampling technique. The results indicate that company size and public accounting firm size have a significant effect on audit delay, while audit tenure and independent commissioners do not have a significant effect on audit delay. Simultaneous testing shows that audit tenure, company size, public accounting firm size, and independent commissioners collectively have a significant effect on audit delay.